PRODUKSI SAMPAH DAN SISTEM PENGELOLAANNYA DI LINGKUNGAN IX KELURAHAN TEGAL SARI 1 KECAMATAN MEDAN AREA TAHUN 2014 - Sikap Berliana Sitepu; Devi Nuraini Santi; Wirsal Hasan (Lingkungan dan Kesehatan Kerja, 2014)
Production Waste and The Waste Management System in Lingkungan  IX Kelurahan Tegal Sari 1 Kecamatan Medan Area in 2014. Waste is any materials unused and rejected as worthless or unwanted, useless or profitless activity, expanding and consuming thoughtlessly or carelessly. Increased activity and human population impact to will give negative health effects which cause environmental degradation. The main purpose of this research  to know the production waste and the waste management in Lingkungan IX Kelurahan Tegal Sari 1 Kecamatan Medan Area .  The research used descriptive survey method and the population was whole household. Sampling was done with a total sampling method ie all households totaling 64 households. Measurement of waste production is done in household by way of weighing the waste for 8 consecutive days. Total waste production obtained is 2.476 litter of 64 households with a head count as many as 243 people or 2,5 m3 . in Lingkungan IX the production waste is 2,5 m3, it’s mean that Lingkungan IX need 1 unit a transporting waste carts so that all the waste can be better. As a result, the average waste production per day was 1,27 Liter / person / day. The resulted of this research  showed that people in Lingkungan IX Kelurahan Tegal Sari 1 Kecamatan Medan Area already has most of the area where waste disposal (96.9%) and the waste disposal have not a close (79,7%). Therefore, the goverments is expected to give more attention and  proper waste management system. Medan City Sanitation Department is expected to add tools such as transporting waste carts, adding janitor and provide information to the community and the janitor better waste management. To the community are also expected to provide shelter waste. Key Words: Waste Management System,  Production Waste,  Tegal Sari 1